Analisis Kemampuan Spasial Siswa Berdasarkan Gaya Kognitif Field Independence dan Field Dependence pada Materi Geometri - Husni Sabil; Sela Michella O. U. Simanjuntak; Dewi Iriani; Ranisa Junita (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
This study analyzes students' spatial abilities based on Field Independence (FI) and Field Dependence (FD) cognitive styles in the context of geometry learning. The research background is a difficulty that is often faced by students with the FD cognitive style in understanding geometric concepts. The main purpose of this study is to compare the spatial abilities of FI and FD students and identify the factors that cause the difficulties of FD students. This study uses a qualitative approach with a descriptive method. The research subject involved 6 students, consisting of 3 FI students and 3 FD students, who were selected using a purposive sampling technique based on the results of the Group Embedded Figures Test (GEFT). Data were collected through interviews, observations, and tests, then analyzed in a qualitative descriptive manner. The results showed that FI students had superior spatial abilities compared to FD students, meeting the indicators of spatial perception, visualization, mental rotation, spatial relationships, and spatial orientation. In contrast, FD students have difficulty meeting most of these indicators. Factors that contribute to FD students' difficulties include dependence on the environment, lack of self-confidence, and lack of understanding of prerequisite materials. This study provides important implications for more effective learning strategies in overcoming students' difficulties in learning geometry, especially by considering the differences in students' cognitive styles.